Enantioselective Functionalization of Enamides at the β‐Carbon Center with Indoles. Issue 47 (23rd October 2018) - Saputra, Mirza A.; Nepal, Binod; Dange, Nitin S.; Du, Pu; Fronczek, Frank R.; Kumar, Revati; Kartika, Rendy
Abstract: We report an enantioconvergent approach for the functionalization of enamides at the β‐carbon atom, which involves a chiral Brønsted acid induced tautomerization of 2‐amidoallyl into 1‐amidoallyl cations. These putative reactive intermediates were produced by ionization of racemic α‐hydroxy enamides with a chiral Brønsted acid and captured with substituted indoles in a highly regio‐ and enantioselective manner. Abstract : An enantioconvergent approach for the functionalization of enamides at the β‐carbon atom is enabled by a chiral Brønsted acid induced tautomerization of 2‐amidoallyl into 1‐amidoallyl cations. These putative reactive intermediates were produced by ionization of racemic α‐hydroxy enamides with a chiral Brønsted acid and captured with substituted indoles in a highly regio‐ and enantioselective manner.